Thermal and Optical Analysis of a Passive Heat Recovery and Storage System for Greenhouse Skin. (2016) - Liu, Xiao; Gao, Hao; Sun, Yanyi; Wu, Yupeng; Martin, Benjamin; Chilton, John; Mirzaei, Parham; Zhang, Xingxing; Beccarelli, Paolo; Lau, Benson
Abstract: The thermal performance of a greenhouse can be greatly affected by the thermal and optical properties of its envelope system. In this study, a novel skin for greenhouse consisting of ethene-co-tetrafluoroethene (ETFE) membrane and Phase Change Material (PCM) RT28 has been developed and has also been experimentally investigated. The optical behaviour of the developed ETFE-Phase Change Material module sample is measured using a spectrometer and a pyranometer, respectively. The results show that at liquid state, the module has higher transmittance than that of at solid state. In addition, the light transmittance is related to the PCM's temperature. In the thermal aspect, the ETFE-Phase Change Material module presents different characterisation under various irradiances. Comparative analysis is also conducted for the ETFE-Phase Change Material, ETFE-water and ETFE alone. The ETFE-Phase Change Material system shows a benefit of the thermal management than that of other systems.